BRAZIL AND ARGENTINA NUCLEAR PROGRAMS DEVELOPMENT UNDER THE COLD WAR DYNAMICS - André Luiz Cançado Motta; José Paulo Silva Ferreira (Revista Conjuntura Austral, 2023)
This article seeks to verify whether the development of the nuclear programs in Brazil and Argentina was influenced by the rise of military regimes in both countries, especially by the context of the Cold War. To this end, this research has a qualitative nature, which takes as its method the bibliographic review of articles, books, theses, and dissertations, to analyse the nuclear programs of both countries and the impacts of the Cold War upon them. It was found that while in the literature on the History of International Relations it is commonly reported that during the Cold War, regions peripheric to the poles of power, such as Latin America, were completely subject  to the pressures of the United States and the Soviet Union, it is proposed that at least regarding nuclearization, there were disputes between the main regional powers (Brazil and Argentina) with the United States about policies to be implemented as well as the diversification of partnerships in pursuit of technological transfer. In addition, it was noticed that the mutual distrust between Brazil and Argentina regarding the degree of development and real intentions underscoring their respective nuclear programs brought about a Cold War like dynamics in the Southern Cone.